La gestión y dirección de la autoridad, en el desarrollo institucional del Colegio Técnico Agropecuario Manú, de la parroquia Manú, cantón Saraguro, provincia de Loja, periodo lectivo 2012 - 2013 - Jumbo Sarango, María Vicenta (2015)
The investigation work developed on the incidence of the Management and Address of the authority, in the Institutional Development, of the Technical Agricultural School Manú, was carried out it with the purpose of toasting to the directive strategies, appropriate and competitive alternatives for of this way to offer an efficient service to the educational community, with the achievement of the goals and objectives required for the good operation of the school center, where it allows him/her to compete with other educational establishments and this way to improve the education with efficiency and of quality. This work had as general objective: To determine the incidence of the management and address of the authority, in the institutional development of the Technical Agricultural School Manú, of the parish Manú, canton Saraguro, county of Loja, period 2012-2013. , which completed it to him by means of the execution of the specific objectives: To analyze the incidence of the management of the authority in the institutional development, of the Technical Agricultural School Manú. To explain the incidence of the address of the authority in the institutional development, of the Technical Agricultural School Manú. To outline alternative limits to overcome the deficiencies in the process of the management, address of the authority and to contribute to the institutional development, of the Technical Agricultural School Manú They were used the inductive, deductive, analytic, synthetic and statistical method; the techniques as the interview and the surveys applied to the educational community, allowing to know like it is the management and address on the part of the authority, to analyze the obtained results and to determine the due conclusions and recommendations. They are also topics on the Management, Address and Institutional Development, theoretical foundation that I contribute to the development of the work. With the results obtained during the development of the investigative process you could evidence that the management and address of the authority of the educational center is not very defined therefore its collaborators manifest that the plannings, qualifications, works in team, communication and other factors that are important for the invigoration of the institution have not negotiated them and addressed in a systematic way with the purpose of enriching the processes pedagogic, administrative etc., this allowed to offer to the authority an outline of limits and appropriate alternatives of how to take a management and efficient address to overcome the institutional problem.